Unlocking the potential of railways a railway strategy for CAREC, 2017 2030. (Regional cooperation strategy and programs., 2017)
This publication provides a blueprint for sound, long term development of CAREC railways into a quick, efficient, and accessible transport system. The 2017 2030 CAREC railway strategy intends to equip the region railways to better capture evolving trade flows and contribute to regional economic development by improving rail and multimodal infrastructure and commercializing and reforming railway activities.